2016
DOI: 10.1246/bcsj.20160053
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Absolute Stereocontrol in Pd-Catalyzed [3+2] Cycloaddition of Oxazolidinones and Trisubstituted Alkenes Using Chiral Ammonium–Phosphine Hybrid Ligands

Abstract: The development of a Pd-catalyzed highly enantio-and diastereoselective [3+2] cycloaddition of 5-vinyloxazolidinones and activated trisubstituted alkenes is described in detail. This protocol for the single-step construction of densely functionalized pyrrolidines with three contiguous stereocenters including vicinal quaternary stereocenters depends on the remarkable ability of phosphine ligands possessing a chiral ammonium ion to promote intermolecular cycloaddition reactions with a precise control of absolute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Previous work demonstrated that the Pd-catalyzed decarboxylative construction of quaternary carbon centers is feasible via the reaction of an external electrophile with a vinyl cyclic carbonate/carbamate under mild reaction conditions (Scheme a). The key to the success of these transformations is the in situ formation of a zwitterionic π-allyl-Pd intermediate upon CO 2 extrusion. As part of our ongoing research work on the transformations of cyclic carbonates, we developed a conceptually novel approach involving the use of nucleophiles toward the synthesis of Z -stereoselective allylic manifolds through a judicious choice of the catalyst source and ligand . The mechanistic rationale based on density functional theory (DFT) calculations suggested that a six-membered palladacycle intermediate is crucial to control the stereoselectivity of the process (Scheme b).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work demonstrated that the Pd-catalyzed decarboxylative construction of quaternary carbon centers is feasible via the reaction of an external electrophile with a vinyl cyclic carbonate/carbamate under mild reaction conditions (Scheme a). The key to the success of these transformations is the in situ formation of a zwitterionic π-allyl-Pd intermediate upon CO 2 extrusion. As part of our ongoing research work on the transformations of cyclic carbonates, we developed a conceptually novel approach involving the use of nucleophiles toward the synthesis of Z -stereoselective allylic manifolds through a judicious choice of the catalyst source and ligand . The mechanistic rationale based on density functional theory (DFT) calculations suggested that a six-membered palladacycle intermediate is crucial to control the stereoselectivity of the process (Scheme b).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, previous work on the Pd-catalyzed decarboxylation of vinyl carbonate A /carbamate B gained great success in preparation of a huge range of useful and otherwise synthetically challenging O - or N -heterocycles (Scheme a). Vinyl benzoxazinanones also showed excellent reactivity under transition metal catalysis resulting in tetrahydroquinolines (Scheme b) . The key to success of these transformations is the in situ generation of zwitterionic π-allyl-Pd intermediate t1 or t2 from the cyclic vinyl carbonate/carbamate precursors upon CO 2 extrusion (Scheme a,b). ,, Thus, to design reactive precursors toward the formation of novel zwitterionic intermediates is essential for the efficient and diverse construction of interesting and valuable cyclic structures.…”
mentioning
confidence: 96%
“…Catalytic generation of zwitterion/dipole intermediates and further cyclization with different acceptors proves to be one of the most powerful strategies in this event. , Specifically, transition metal catalyzed decarboxylative reactions for this purpose have attracted much research interest and advanced remarkably as a result of their advantages of easy operations, redox neutrality, and only CO 2 -byproduct generation . In this sense, previous work on the Pd-catalyzed decarboxylation of vinyl carbonate A /carbamate B gained great success in preparation of a huge range of useful and otherwise synthetically challenging O - or N -heterocycles (Scheme a). Vinyl benzoxazinanones also showed excellent reactivity under transition metal catalysis resulting in tetrahydroquinolines (Scheme b) . The key to success of these transformations is the in situ generation of zwitterionic π-allyl-Pd intermediate t1 or t2 from the cyclic vinyl carbonate/carbamate precursors upon CO 2 extrusion (Scheme a,b). ,, Thus, to design reactive precursors toward the formation of novel zwitterionic intermediates is essential for the efficient and diverse construction of interesting and valuable cyclic structures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 5-Vinyloxazolidin-2-ones as the vinylaziridine equivalent have recently been applied to Pd-catalyzed decarboxylative allylic cycloadditions with unsaturated electrophiles with high efficiency (Scheme 1a). 5 Most recently, Tunge and Wang reported Pd-catalyzed asymmetric allylic cycloaddition of vinyl benzoxazinanones with Michael acceptors to provide hydroquinolines with high enantio-and diastereoselectivities. 6 Subsequently, vinyl benzoxazinanones have served as useful 1.4-C,N-dipoles in Pd-catalyzed decarboxylative allylic cycloadditions with a variety of reaction partners to form azaheterocycles with diverse functionalities (Scheme 1b).…”
mentioning
confidence: 73%